Isolated peripheral neuroleukemiosis mimicking Guillain‐Barré syndrome in an adolescent with relapsed B‐lymphoblastic leukemia - Ethan Edmondson; Paisley Pauli; Jyotinder Punia; Daniel G. Calame (Annals of the Child Neurology Society, 2024)
Abstract Background Neuroleukemiosis, leukemic infiltration of the peripheral nervous system (PNS), is rare. Very few cases of isolated neuroleukemiosis, PNS leukemic infiltration without leukemia blasts in the blood or bone marrow, have been reported in pediatrics. Most cases have occurred in adults with acute myelogenous leukemia (AML) in remission who presented with peripheral neuropathy. We describe a pediatric patient presenting with isolated neuroleukemiosis mimicking Guillain‐Barré syndrome. Patient description A 15‐year‐old boy presented 1 month after IVIG treatment for Guillain‐Barre syndrome with worsening ataxia and weakness. He had a past medical history of B‐cell acute lymphoblastic leukemia (B‐ALL) in remission for 8 years. Examination revealed distal greater than proximal weakness of the bilateral lower extremities, areflexia at the Achilles tendon, and 1+ patellar and upper extremity reflexes. Initial magnetic resonance imaging (MRI) of the brain and spine were normal, and lumbar puncture revealed increased protein with uninterpretable white count due to excessive red blood cells. Repeat MRI brain and spinal cord showed extensive enlargement of all nerve roots and enhancement of the cauda equina and portions of cranial nerve VII bilaterally. Repeat lumbar puncture with cytology revealed leukemic blast cells. Blasts were not detected in peripheral blood smear or by flow cytometry. Bone marrow biopsy was also free of blast cells, confirming the diagnosis of relapsed B‐ALL restricted to the nervous system. Conclusions Neuroleukemiosis is a rare entity with typical clinical features of mono‐ or polyneuropathy. It most often occurs in adults in remission from AML. However, neuroleukemiosis should also be on the differential for pediatric patients in remission from ALL presenting with neuropathy.